Histopathological pattern of ovarian neoplasms in Sub-Himalayan belt of rural India: a four-year study from a tertiary care teaching hospital - Sharma, Manupriya; Soni, Anjali; Kaul, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ovarian tumors are one of the ubiquitous and common forms of neoplasms in women. The aim of the study was to understand the pattern of benign and malignant ovarian neoplasms and their distribution in different age groups in rural population of India. Methods: A retrospective study conducted in the Department of Pathology in close collaboration with Department of Obstetrics and Gynecology, Dr. Rajendra Prasad Government Medical College, Kangra at Tanda (HP), India. All the patients irrespective of age group who were operated for ovarian neoplasms (benign or malignant) were included in this retrospective analysis over duration of four years (2013 to 2016). “WHO classification system” was used, for classification of all these ovarian tumors. The incidence of these tumors with respect to age group was also studied. Results: During the study period (2013-2016), there were a total of 242 surgeries for ovarian neoplasms. Of these, majority of the tumours were benign 184 (76%), but an alarming number of women had malignant ovarian tumours 51 (21%), remaining 7 (3%) cases were borderline. Age wise distribution was 7% (16/242) in less than 20 years age, 19% (46/242) in 20-30 years age, 29% (69/242) in 30-40 years age group, 24% (59/242) in 40-50 years and remaining 21% (52/242) in more than 50 years age group. Pre-dominantly benign tumors were surface epithelial tumors (serous/ mucinous cystadenoma), germ cell tumors (mature cystic teratoma) and endometrioma. Major malignant tumors were surface epithelial tumors (serous/mucinous cystadeno-carcinoma), and germ cell tumors (dysgerminoma, immature teratoma). Conclusions: In this sub-Himalayan belt of rural India, the incidence of benign ovarian tumors was 76%. Borderline ovarian tumors were seen in 3% cases and the remaining 21% cases were malignant ones. Even though benign tumors were the commonest for each age group, however as the age of women increased the proportion of malignant tumors in them increased. Surface epithelial tumors are the most common class of tumors in both benign and malignant tumors. Serous cystadenoma is the most common ovarian tumor overall as well as most common benign tumor whereas serous cystadeno-carcinoma is most common malignancy. Stromal ovarian tumor (one case) is a rarity. Only one woman had bilateral ovarian tumor.